EFFECT OF DISCIPLINE WORK AND WORK MOTIVATION ON EMPLOYEE PRODUCTIVITY AT THE HYATT REGENCY HOTEL YOGYAKARTA - Kurniawati, Elizabeth Dwi; Lantum, MS, Drs. Alex Kahu (Management, 2010)
Any activity is concentrated on the utilization of many human resources that we should bear the company must also give much attention to employees as a reflection of the principle of mutual cooperation and mutual meguntungkan mendudukung. Employees are intrinsically ordinary man who did not escape the feeling lazy, tired and less satisfied with the situation. If such attitudes are left and continue, it will affect the company is lowering labor productivity and corporate image. To comply with labor standards, the management held a planning effort to meet company standards by conducting selection. So the successful conduct of the task is not arise haphazardly, but success is also heavily influenced by the presence of business improvement. Therefore in order to achieve task success rate of employees, management need to apply the motivational system that is supported by the attitude of labor discipline. With the discipline of work, the company adds value to the productivity of its work so that the company will be able to compete in labor quality and quality of product quality. From these results it can increase work productivity. From the description that has been said, it can be summarized that with the good work discipline and the motivation of a supportive working well, according to the activities carried out it will affect and cause the quality of human resources well so that will increase labor productivity of an organization or company. Keywords : discipline work, work motivation, employee productivity